Pengembangan Modul Pembelajaran Berbasis Sensor Inertial Measurement Unit (IMU) untuk Meningkatkan Keterampilan Teknik Tendangan Sepak Bola Mahasiswa Pendidikan Jasmani - Irawan, Yogi Ferdy (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The development of sensor technology in sports education opens new opportunities to improve the quality of learning motor skills techniques. This study aims to develop a learning module based on Inertial Measurement Unit (IMU) sensors to improve football kicking technique skills among Physical Education students. This research uses the Research and Development (R&D) method with the ADDIE model conducted from January to March 2025 at the Physical Education, Health and Recreation Study Program, Ma'arif Nahdlatul Ulama University Kebumen. The research subjects consisted of 40 fourth-semester students divided into an experimental group (n=20) and a control group (n=20). Research instruments included MPU-6050 IMU sensors, an Android-based mobile application, kicking technique assessment rubrics, and user response questionnaires. The results showed that the IMU sensor-based learning module effectively improved students' football kicking technique skills. The experimental group experienced an increase in average scores from 65.4 to 82.7 (p<0.001), while the control group increased from 64.8 to 71.3 (p<0.05). There was a significant difference between groups in the post-test (p<0.001) with Cohen's d effect size of 2.18 (very large category). Expert validation showed that the learning module obtained a score of 4.6 out of 5.0 (very feasible category). Student responses showed a satisfaction level of 89.2%.